Synergistic role of quercetin and vitamin E against gentamycin induced nephrotoxicity - S.ARULRAJA,; S.RAJARAM,; G.KARTHIKEYAN, (International Journal of Pharma and Bio Sciences, 2019)
Gentamicin (GM) is an antibiotic extensively used in the treatment of bacterial infections; though its use is restricted because of nephrotoxicity. Numerous studies show that free radicals are significant mediators of gentamicin induced nephrotoxicity. Therefore, the present investigation was to explore the probable protective role of the flavonoid quercetin and vitamin E alone/combinational on gentamicin-induced nephrotoxicity. Rats were divided into five groups, group I served as a control; group II was administered with gentamycin; Group 3 animals treated with gentamycin with Quercetin; Group 4 animals treated with gentamycin and Vitamin E; Group 5 animals treated with gentamycin with quercetin and Vitamin E for 45 days. After that, the samples were collected for biochemical analysis. Then animals were anaesthetized with anesthetic ether and their blood samples were collected through retro orbital puncture/tail vein and the serum will be separated and subjected to biochemical analysis. The levels of blood components such as WBC, RBC, Hemoglobin, lymphocytes and mean cell volume (MCV) decreased in gentamycin treated groups and these levels became normal upon synergistic treatment with quercetin and vitamin E. Similar results were observed on the levels of urea, uric acid, creatinine, protein, total cholesterol, free cholesterol, triglycerides, free fatty acids, phospholipids as well as lipid peroxidation. Thus, these results obviously prove the vital role of oxidative stress and its association to renal dysfunction, and also reveals that the therapeutic prospective of quercetin and vitamin E could exhibit as synergistic action against gentamycin induced nephrotoxicity.